A multipurpose thermal vacuum chamber for planetary research compatible with stand-off laser spectroscopies - Laserna-Vázquez, José Javier; Álvarez-Llamas, César; Purohit, Pablo; Moros-Portolés, Javier; Lucena, Patricia; Vadillo-Pérez, José Miguel (My University, 2022)
Stand-off spectroscopies and imaging techniques have gained a proper niche within the modern tools in remote compositional analysis for exploration in-situ planetary surface using rovers. Laser-induced breakdown spectrometry (LIBS), Raman spectroscopy, time-resolved laser-induced fluorescence (LIF) and laser-induced shockwave acoustic monitoring are tools currently installed and used at the Perseverance Curiosity and rover in the seek of understanding mineralogy and geochemistry of Mars, as they obtain real-time information at distances up to 12 meters. The abstract details the TVC designed and installed at UMALASERLAB to serve the astrochemical community. With a length of 12 meters and an useful internal diameter of 1,6 meters, the chamber operates in a temperature range between 200 K - 400 K and can be oil-free pumped down from atmospheric pressure to 10 mbar in the current -4configuration. Additional upgrades may extend the pressure range up to the 10 mbar -6 range. Such dimensions and figures turns the TVC of UMALASERLAB into a powerful and versatile facility for space-related studies in chemistry, biology and engineering
Keywords: Planetas - Exploración; LIBS; Acoustic; Rocks; Minerals; Mars